From egg to slaughter: monitoring the welfare of Nile tilapia, Oreochromis niloticus, throughout their entire life cycle in aquaculture - Pedrazzani, Ana Silvia; Cozer, Nathieli; Quintiliano, Murilo Henrique; Tavares, Camila Prestes dos Santos; Biernaski, Vilmar; Ostrensky, Antonio (Frontiers in Veterinary Science, 2023)
The primary aim of this study was to comprehensively evaluate the welfare of Nile tilapia (Oreochromis niloticus) throughout their entire life cycle within aquaculture, spanning from reproduction to slaughter. The methodology was structured to identify welfare indicators closely aligned with the principles of animal freedoms defined by the Farm Animal Council, encompassing environmental, health, nutritional, behavioral, and psychological freedom. Notably, psychological freedom was inherently considered within the behavioral and physical analyses of the animals. To accomplish this, an integrative systematic literature review was conducted to define precise indicators and their corresponding reference values for each stage of tilapia cultivation. These reference values were subsequently categorized using a scoring system that assessed the deviation of each indicator from established ideal (score 1), tolerable (score 2), and critical (score 3) ranges for the welfare of the target species. Subsequently, a laboratory experiment was executed to validate the pre-selected health indicators, specifically tailored for the early life stages of tilapia. This test facilitated an assessment of the applicability of these indicators under operational conditions. Building on the insights gained from this experimentation, partial welfare indices (PWIs) were computed for each assessed freedom, culminating in the derivation of a general welfare index (GWI). Mathematical equations were employed to calculate these indices, offering a quantitative and standardized measure of welfare. This approach equips tilapia farmers and processors with the tools necessary for the continuous monitoring and enhancement of their production systems and stimulate the adoption of more sustainable and ethical practices within the tilapia farming.